COMMUNICATIVE STRATEGY IN POLITICAL DIALOGUE - Razakova Nargiza Xursanboyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Politics and communication cannot be separated in a democracy. Politicians and political parties must convince voters of their ideas and proposals and try to organize, from them, sufficient majorities to achieve power.